2017
DOI: 10.1186/s13041-017-0322-y
|View full text |Cite
|
Sign up to set email alerts
|

The ERM protein Moesin is essential for neuronal morphogenesis and long-term memory in Drosophila

Abstract: Moesin is a cytoskeletal adaptor protein that plays an important role in modification of the actin cytoskeleton. Rearrangement of the actin cytoskeleton drives both neuronal morphogenesis and the structural changes in neurons that are required for long-term memory formation. Moesin has been identified as a candidate memory gene in Drosophila, however, whether it is required for memory formation has not been evaluated. Here, we investigate the role of Moesin in neuronal morphogenesis and in short- and long-term… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 63 publications
(97 reference statements)
2
19
0
Order By: Relevance
“…Furthermore, other studies have revealed that changes in dendritic complexity impaired LMC (Freymuth & Fitzsimons, 2017;Lee et al, 2017). Both the microinjection of dme-miR-92b antagomirs and overexpression of crebA in D. melanogaster did result in significant increase of LMC (Bi et al, 2019), further supporting a miRNA-target pathway that regulates the change of LMC in Drosophila induced by Wolbachia infection.…”
Section: Effect Of Wolbachia On Learning and Memory Capacity (Lmc) Inmentioning
confidence: 70%
“…Furthermore, other studies have revealed that changes in dendritic complexity impaired LMC (Freymuth & Fitzsimons, 2017;Lee et al, 2017). Both the microinjection of dme-miR-92b antagomirs and overexpression of crebA in D. melanogaster did result in significant increase of LMC (Bi et al, 2019), further supporting a miRNA-target pathway that regulates the change of LMC in Drosophila induced by Wolbachia infection.…”
Section: Effect Of Wolbachia On Learning and Memory Capacity (Lmc) Inmentioning
confidence: 70%
“…NKX6.3/HGTX over-expression also led to a reduction of whole-body triglyceride (TAG) content. While this was surprising, this observation is not uncommon in functional screens 60,61 and it suggests that a tight NKX6.3 / HGTX gene dosage is important to maintain TAG levels.…”
Section: Discussionmentioning
confidence: 91%
“…MSN can inhibit the function of RhoA and is closely associated with the Rac1 pathway [Freymuth & Fitzsimons, 2017]. MSNP1AS overexpression enhanced RhoA activity and downregulated Rac1 activity, whereas when MSNP1AS expression was inhibited, the activities of RhoA and Rac1 showed the opposite trend [Fig.…”
Section: Resultsmentioning
confidence: 99%